A survey on squatter residents problems in Tabuan Foochow, Kuching / Belenyun Medan ... [et. al] - Medan, Belenyun; Siba, Magdelene; David, Spencer Egat; Noet, Suwi; Jaret, Winie (2004)
Squatter problem is not a new phenomenon exist as a consequences of the development of the country and the economic growth of the country. This problem can be assumed as a “development diseases” if there are no measures taken to overcome to and can give a bad implication to our country.